Angklung Music-Based Collaborative Learning Management Strategy from an Islamic Education Perspective - Wathon, A (Pendidikan Islam Anak Usia Dini STIT Palapa Nusantara, 2026)
Although recognition of collaborative learning and culturally responsive pedagogy is increasing, the specific integration of traditional musical instruments such as the angklung into structured collaborative learning management strategies, particularly from the perspective of Islamic education, remains severely underexplored. This study aims to analyze the potential and implications of angklung-based collaborative learning management strategies for promoting the holistic development of students in Islamic educational institutions. Employing a qualitative research design, the study explores how the inherently collaborative nature of angklung performance, when guided by the principles of Islamic pedagogy, can enhance learning outcomes, develop socio-emotional skills, and cultivate spiritual values among students. Preliminary findings indicate that such strategies are capable of improving teamwork, communication, and discipline, while simultaneously deepening students’ appreciation of cultural heritage and Islamic ethics. The integration of angklung into the curriculum provides a unique platform for experiential learning that is aligned with the holistic philosophy of tarbiyah (education) in Islam. The study concludes by affirming the crucial role of culturally sensitive and spiritually grounded educational practices in contemporary Islamic education and advocates the adoption of innovative strategies that harness local arts. The implications of this research include theoretical contributions to the development of culturally responsive pedagogy and Islamic education management, practical guidelines for educators in implementing such strategies, and the opening of a future research agenda on the long-term impact of Islamic education integrated with the arts.